New Insights into Fracture Process through In-Situ Acoustic Emission Monitoring During Fatigue Hydraulic Fracture Experiment in Äspö Hard Rock Laboratory. (2017) - Kwiatek, Grzegorz; Plenkers, Katrin; Martínez-Garzón, Patricia; Leonhardt, Maria; Zang, Arno; Dresen, Georg
Abstract: In this study we analyze the nano- and picoseismicity recorded during the Fatigue Hydraulic Fracturing (FHF) in situ experiment performed in Äspö Hard Rock Laboratory, Sweden. The fracturing experiment composed of six fractures driven by three different water injection schemes (continuous, progressive and pulse pressurization) was performed during the year 2015 inside a 28 m long, horizontal borehole located at 410 m depth. The fracturing process was monitored with two different seismic networks covering a wide frequency band between 0.01 Hz and 100000 Hz, including broadband seismometers, geophones, high frequency accelerometers and acoustic emission sensors. The combined seismic network allowed for detection and detailed analysis of nearly 200 seismic events with moment magnitudes MW < -4 that occurred solely during the hydraulic fracturing stages. We relocated the seismic catalog using double-difference technique and calculated the source parameters (seismic moment, source size, stress drop, focal mechanism and seismic moment tensor). The derived physical characteristics of induced seismicity are compared with the stimulation parameters as well as with the geomechanical parameters of the site.